DNA isolation in bark beetles: Reliability of extraction methods and application in downstream molecular procedures - Stazione, Leonardo (2024)
Molecular tools are increasingly used in entomology for several applications such as taxonomy, genetics, ecology and evolution. For these studies, DNA extraction from individual insects is a crucial step, since the yield and quality vary depending on the methods used. Finding an ideal balance between quality and yield is particularly difficult to reach and several constraints must be considered upon selecting the final protocol. Bark beetles (Coleoptera: Curculionidae, Scolytinae) are a diverse group of forest insects for which molecular studies at the individual level are important, given that many species are invasive and may become pests. However, DNA extraction in bark beetles is not easy, given their small size and complex molecules of diverse nature conforming their exoskeleton and present in their digestive tract. Here, we carried out a comparative analysis of DNA extraction performance in five bark beetle species: Hylurgus ligniperda, Hylastes ater, Orthotomicus erosus, Orthotomicus laricis and Cyrtogenius luteus. By assessing the efficiency of two different protocols, our aim was to establish the best species-specific method for population-level studies. Our results showed that a method’s whole performance mainly depends on the species considered and translates into DNA quantity and quality variance. We also noted that the traditional method showed better PCR efficiency for the smallest species whereas the commercial kit performed better for the larger beetles. Our comparative analysis provides evidence that no single method for DNA isolation is best, and that each particular species requires optimization.